Recent Advances in Magnesia Blended Cement Studies for Geotechnical Well Construction—A Review - Chen, Weiqing; Elkatatny, Salaheldin; Murtaza, Mobeen; Mahmoud, Ahmed Abdulhamid (Frontiers in Materials, 2021)
The current paper presents a literature review on the studies of incorporation of magnesia (magnesium oxide) into Portland cement material from the geotechnical well construction perspective. Started with the application conditions comparison between civil construction and geotechnical well cementing, this work reviewed the Portland cement categorizations, magnesia manufacturing routes at first. Then, the physical-chemical-mechanical properties are investigated which includes the reactivity of magnesia, expansion influence from its hydration, and carbonation/dehydroxylation of magnesia blended Portland cement. The development of cement material hydration modeling methods is also summarized. Moreover, the experimental characterization methods have also been elucidated including composition determination, particle size analysis, volumetric variation measurement, compressive strength testing, shear-bond strength testing, transition state analysis, etc. Meanwhile, the results and conclusions were extracted from the literature. Through this route, a comprehensive understanding of the scientific research progress on magnesia blended Portland cement development for geotechnical well construction is derived. Additionally, it is concluded that incorporating magnesia into Portland cement can provide benefits for this material utilization in geotechnical well constructions provided the reasonable tuning among the characteristics of magnesia, the downhole surrounding conditions, and the formulation of the cement slurry. Satisfying these pre-conditions, the effective expansion not only mitigates the micro-annulus issues but also increases the shear bonding strength at the cementing interfaces. Moreover, the caustic magnesia introduction into Portland cement has the potential advantage on carbon dioxide geological sequestration well integrity compared with the Portland cement sheath without it because of the denser in-situ porous matrix evolvement and more stable carbon fixation features of magnesium carbonate. However, since the impact of magnesia on Portland cement strongly depended on its properties (calcination conditions, particle size, reactivity) and the aging conditions (downhole temperature, pressure, contacting medium), it should be noted that some extended research is worth conducting in the future such as the synchronized hydration between magnesia and Portland cement, the dosage limit of caustic magnesia in Portland cement in terms of CO2 sequestration and the corresponding mechanical properties analysis, and the hybrid method (caustic magnesia, Portland cement, and other supplementary cementitious materials) targeting the co-existence of geothermal environment and corrosive medium scenario.